The Role And Authority Of The World Trade Organization (WTO) Towards International Dispute Settlement Seen From The Case Of Indonesia's Nickel Ore Exports With The European Union (EU) - Jessica Valencia (JURNAL HUKUM SEHASEN, 2024)
This research aims to analyze the role and authority of the World Trade Organization (WTO) towards international dispute resolution seen from the case of Indonesia's nickel ore exports with the European Union (EU). This type of research is descriptive analytical. This research was conducted with normative juridical methods sourced from primary legal materials and secondary legal materials which include relevant sources of international law, such as international conventions / treaties, international customs, general legal principles, court decisions, as well as teachings / doctrines of legal experts websites, books and other sources. The data analysis technique in this study collects the data and then analyzes it so that it gives rise to a conclusion. The result of this research is that the World Trade Organization (WTO) as the only international organization (OI) engaged in international trade has an important role for resolving disputes regarding trade because it concerns the world economy. Although basically the WTO is an organization that guarantees smoothness and aims to create good and peaceful international trade, the existence of supporting organs such as the Dispute Settlement Body and the Appellate Body is a concrete manifestation of the WTO's authority in resolving international disputes based on doctrines such as attributed, implied, and inherent power. In the case of Nickel Ore Exports, Indonesia and the European Union can resolve existing disputes through various means offered by the WTO which can be utilized as well as possible, especially to improve relations between the two in terms of trade by using the settlement facilities provided by the organization. However, in finding a way out of the settlement, it should not ignore the function of the WTO which is based on the main principles. One of them is the fact that Indonesia is a developing country which, according to the basic principles of the WTO, is entitled to certain special treatment.